Environmental changes and human impact on landscape development in the Upper Rhine region - Mäckel, Rüdiger; Friedmann, Arne; Sudhaus, Dirk (ERDKUNDE, 2009)
The human impact on the environment of the Upper Rhine region and adjacent mountains (Black Forest and Vosges) is studied on the basis of radiocarbon dated pollen diagrams, archaeological findings and the geomorphological interpretation of geoarchives. The investigations show a much higher level and an earlier begin of human interferences than previously assumed. Preferred settlement and farming areas since the onset of sedentarization and farming during Neolithic Times were the warmer and loess covered areas of the lowlands and foothills. However, also the higher zones of the mid-mountain regions were used during climatically favourable periods (i.e. late Neolithic, Bronze Age, Roman Times). Thus a distinct contrast of the intensity of human impact between the lowlands and the highlands does not exist. It can rather be described as an interaction between different natural regions. Noticeable is the connection between changes in the ratio of woodland and open land and the geomorphodynamic processes. Nine main erosion/sedimentation phases can be distinguished due to different levels of land use intensity.